Moderation of Islamic Education as an Effort to Prevent Radicalism (Case Study of FKUB Singkawang City, Kalimantan, Indonesia) - Asrip Widodo (FITK UIN Walisongo, 2019)
Radicalism threatens harmony and unity. We need a holistic deradicalization effort by various elements of the nation. One element that has a strategic role is the Forum for Religious Harmony (FKUB). The study was conducted to reveal the role of FKUB Singkawang City in campaigning for moderation of Islamic education for the community as an effort to prevent radicalism, thus delivering this city as the number one most tolerant city in Indonesia. The method used is a qualitative field (Field Research), researchers go directly to the field to obtain data and information from data sources. Data were collected through direct interviews with the Chairperson of FKUB Singkawang City, FKUB documentation, Social Media and direct observation to the research location. The results showed that FKUB was able to realize moderation of Islamic education outside of educational institutions with dialogue and advocating strategic.Radikalisme mengancam harmoni dan persatuan. Kita membutuhkan upaya deradikalisasi holistik oleh berbagai elemen bangsa. Salah satu elemen yang memiliki peran strategis adalah Forum Kerukunan Umat Beragama (FKUB). Studi ini dilakukan untuk mengungkap peran FKUB Kota Singkawang dalam mengkampanyekan moderasi pendidikan Islam bagi masyarakat sebagai upaya mencegah radikalisme, sehingga menjadikan kota ini sebagai kota nomor satu yang paling toleran di Indonesia. Metode yang digunakan adalah bidang kualitatif (Field Research), peneliti pergi langsung ke lapangan untuk memperoleh data dan informasi dari sumber data. Data dikumpulkan melalui wawancara langsung dengan Ketua FKUB Kota Singkawang, dokumentasi FKUB, Media Sosial dan observasi langsung ke lokasi penelitian. Hasil penelitian menunjukkan bahwa FKUB mampu mewujudkan moderasi pendidikan Islam di luar lembaga pendidikan dengan dialog dan advokasi strategis.